Modern inorganic pharmaceutical chemistry - Discher, Clarence A.; Medwick, Thomas ;Bailey, Leonard C. (Prospect Heights, Ill. : Waveland Press, Inc., 1985)
In this new edition the arrangement and general chemical background have rmained essentially unchanged. When necessary, chemical advances and changes in practice have been introduced.
Part I: Modern concepts of chemical reactions -- Part II: Inorganic chemistry in teh practice of pharmacy -- Part III: Inorganic substances as medicinal agents
Includes index.
Keywords: PHARMACEUTICAL PHARMACIES